2020
DOI: 10.1111/acel.13263
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differences and longevity‐related phenotypes influence lifespan and lifespan variation in a sex‐specific manner in mice

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(34 citation statements)
references
References 47 publications
3
31
0
Order By: Relevance
“…To compare neuropathology and neuroinflammatory signatures in BALB/c and C57BL/6 mice during chronic infection, NanoString analysis was conducted on BALB/c mouse brain RNA using the same time points of infection as before. Results of merged BALB/c vs. C57BL/6 analysis demonstrate initial differences in gene expression between naïve mice ( Figure 6A ) consistent with previous analysis ( Sellers et al., 2011 ; Yuan et al., 2020 ). In contrast to B6 mice which generally show a continued increase in gene change over the course of infection, BALB/c mice exhibit the largest change at 14dpi which then returns to patterns similar to naïve at chronic infection.…”
Section: Resultssupporting
confidence: 89%
“…To compare neuropathology and neuroinflammatory signatures in BALB/c and C57BL/6 mice during chronic infection, NanoString analysis was conducted on BALB/c mouse brain RNA using the same time points of infection as before. Results of merged BALB/c vs. C57BL/6 analysis demonstrate initial differences in gene expression between naïve mice ( Figure 6A ) consistent with previous analysis ( Sellers et al., 2011 ; Yuan et al., 2020 ). In contrast to B6 mice which generally show a continued increase in gene change over the course of infection, BALB/c mice exhibit the largest change at 14dpi which then returns to patterns similar to naïve at chronic infection.…”
Section: Resultssupporting
confidence: 89%
“…Lifespan studies of the ITP demonstrate that, when following precise standards, mouse lifespan can be reproducibly extended by drugs in the diet (Harrison et al, 2009(Harrison et al, , 2014(Harrison et al, , 2019Miller et al, 2011Miller et al, , 2014Miller, Harrison, et al, 2020;Strong et al, 2008Strong et al, , 2016.…”
Section: F I G U R E 3 Lifespan Curves Of Controls and The 4 Interventions Without Effects/mentioning
confidence: 99%
“…The 2015 cohort of UM-HET3 mice was also used to test the effects of canagliflozin, an inhibitor of SGLT2 (Miller, Harrison, et al, 2020).…”
Section: Control and Experimental Dietsmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we found some sex‐specific loci related to longevity. Numerous studies have reported remarkable sex differences in longevity and life span (Austad & Fischer, 2016; Candore et al, 2006; Ostan et al, 2016; Yuan et al, 2020); however, very few studies have reported the sex‐differential effect of genetics for longevity. TOMM40/APOE is well‐characterized longevity locus that could be split into 4 LD blocks.…”
Section: Discussionmentioning
confidence: 99%